2020
DOI: 10.1002/anie.202008262
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of TY‐Phos and Application in Palladium‐Catalyzed Enantioselective Fluoroarylation ofgem‐Difluoroalkenes

Abstract: The first example of highly enantioselective fluoroarylation of gem-difluoroalkenes with aryl halides is presented by using a new chiral sulfinamide phosphine (Sadphos) type ligand TY-Phos. N-Me-TY-Phos can be easily synthesized on a gram scale from readily available starting materials in three steps. Salient features of this work including readily available starting materials, good yields, high enantioselectivities as well as broad substrate scope make this approach very practical and attractive. Notably, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 101 publications
1
46
0
Order By: Relevance
“…2 ). The gold complexes derived from Ming-Phos 42 , 43 , 54 56 , Xu-Phos 57 61 , Xiang-Phos 62 65 , PC-Phos 41 , 66 68 and TY-Phos 69 could deliver (−)- 2aa in up to 83% yield with 85% ee. We found that enantioselectivity roughly correlates to the electrical properties of the Sadphos, with a more σ-donating ligand providing a higher enantioselectivity and catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). The gold complexes derived from Ming-Phos 42 , 43 , 54 56 , Xu-Phos 57 61 , Xiang-Phos 62 65 , PC-Phos 41 , 66 68 and TY-Phos 69 could deliver (−)- 2aa in up to 83% yield with 85% ee. We found that enantioselectivity roughly correlates to the electrical properties of the Sadphos, with a more σ-donating ligand providing a higher enantioselectivity and catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…5 This difference in solventbonding drove the selectivity of inter-and intramolecular decomposition of the hypoperoxy intermediate, which in turn generated the alcohol or ketone products, respectively. Further evidence for this mechanism was provided by 18…”
Section: Scheme 22 Acid-catalyzed Hydrofunctionalization Of Gem-difluoroalkenesmentioning
confidence: 90%
“…The absolute configuration of TY-Phos was unambiguously determined via X-ray crystallography analysis. [24] Further screening of the palladium salts, reaction temperatures and solvents failed to give better results either (Supporting Information, Table S1). The optimal reaction conditions are described as follows: [allylPdCl] 2 as the catalyst, N-Me-TY9 as the chiral ligand in cyclohexane at 70 8C for 16 h. Having the optimal reaction conditions in hand, we first investigated the generality of the aryl halides (Scheme 4).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The absolute configuration of (S)-4 ae was unambiguously determined via X-ray crystallography analysis. [24] Notably, the aryl bromides are also suitable for this reaction (4 ac, 4 ae, 4 ah, 4 ai, and 4 ak). The reaction showed a high chemoselectivity when the aryl halides contain both iodide and bromide (4 aj, 4 ar), in which the reaction selectively take place at the iodide position.…”
Section: Angewandte Chemiementioning
confidence: 99%